Suburban creativity: The geography of creative industries in Johannesburg - Gregory, James J.; Rogerson, Christian M. (Bulletin of Geography. Socio-economic Series, 2018)
Creativity is an increasing scholarly focus for urban and economic geographers. The aim in this paper is to contribute to what is so far mainly a Northern literature around the locational characteristics of creative industries. The results are analysed from a comprehensive audit undertaken of creative industries in Johannesburg, South Africa’s leading economic hub. In common with certain other investigations of creative industries the largest component of enterprises in Johannesburg is creative services involving the production of goods or services for functional purposes. An aggregate picture emerges of the geography of creative industries in Johannesburg as strongly focused in suburban areas rather than the inner-city and its fringe areas. Nevertheless, certain differences are observed across the eight categories of creative industries. The evidence concerning the spatial distribution of creative industries in Johannesburg provides a further case for re-positioning the suburbs in post-Fordist debates around creative city economies and for re-examining neo-liberal cultural policies that preference inner-city areas.